Sequential Infection with Common Pathogens Promotes Human-like Immune Gene Expression and Altered Vaccine Response - Reese, Tiffany A; Bi, Kevin; Kambal, Amal; Filali-Mouhim, Ali; Beura, Lalit K; Bürger, Matheus C; Pulendran, Bali; Sekaly, Rafick-Pierre; Jameson, Stephen C; Masopust, David; Haining, W Nicholas; Virgin, Herbert W (Cell host & microbe, 2016)
Immune responses differ between laboratory mice and humans. Chronic infection with viruses and parasites are common in humans, but are absent in laboratory mice, and thus represent potential contributors to inter-species differences in immunity. To test this, we sequentially infected laboratory mice with herpesviruses, influenza, and an intestinal helminth and compared their blood immune signatures to mock-infected mice before and after vaccination against yellow fever virus (YFV-17D). Sequential infection altered pre- and post-vaccination gene expression, cytokines, and antibodies in blood. Sequential pathogen exposure induced gene signatures that recapitulated those seen in blood from pet store-raised versus laboratory mice, and adult versus cord blood in humans. Therefore, basal and vaccine-induced murine immune responses are altered by infection with agents common outside of barrier facilities. This raises the possibility that we can improve mouse models of vaccination and immunity by selective microbial exposure of laboratory animals to mimic that of humans.